ID Galerie. - Kunstverein Lingen, Lingen (Lingen : Kunstverein Lingen, 1994)
Bramlette, Teresa ; Eller, Thomas ; Hahn, Wolfgang ; Hausmann, Till ; Imbach, Samuel ; Inger, Gereon ; Inhestern, Hans-Georg ; Jansen, Marcus ; Kantor, Zvika ; Krondl, Michael ; Laugs, Martha ; Leibowitz, Cary S. ; Loermann, Vera ; Martin, Bernhard ; Zey, Georg
ID Galerie zu gast im Kunstverein Lingen, 15.1. - 13.2.1994
boek